Analisis Kinerja Keuangan Dan Pengaruhnya Terhadap Kemampuan Penyaluran Kredit Pada Bank Danamon, Tbk - Nur Fetiningsih Syaframis; Puji Muniarty (Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to determine and analyze financial performance and its influence on the ability to disburse credit at Bank Danamon, Tbk. The research method used is quantitative associative research. The sample of this research consists of balance sheet and profit and loss statements for 15 years from the period 2006 - 2020 with the sampling technique used is purposive sampling. The analytical tools used are classical assumptions, multiple linear regression, Coefficient of Determination, Partial Test, and Simultaneous Test which aims to analyze the relationship between the CAR, NPL, and LDR variables on the ability to provide credit using SPSS v software. 23. The results of this study indicate that CAR and NPL have a significant effect on Credit Disbursement Capability, for LDR it has no and no significant effect on Credit Distribution Capability.